Evidence for genomic imprinting of the major QTL controlling susceptibility to trypanosomiasis in mice - Clapcott, S.J.; Teale, A.J.; Kemp, Stephen J. (Wiley, 2000)
Inbred strains of laboratory mice exhibit marked differences in survival time following infection with Trypanosoma congolense, the principal cause of trypanosomiasis in African livestock.The difference in survival time between the relatively resistant C57BL/6 J and more susceptible BALB/c inbred strains has been attributed to three quantitative trait loci (QTLs), Tir1, Tir2 and Tir3. In order to determine whether there was a parent-of-origin effect on this trait, four backcross populations derived from the C57BL/6 J and BALB/c parental strains were bred and inoculated with T. congolense. The two populations with F1 fathers and BALB/c mothers had a signi®cantly greater overall survival rate than the two populations with BALB/c fathers and F1 mothers. This pattern of inheritance suggested the involvement of imprinted genes. Genotyping with markers at the three QTLs controlling susceptibility revealed that the difference in survival time was consistent with genomic imprinting of the QTL of largest effect, Tir1.